Assessing the contribution of vegetation variation to streamflow variation in the Lancang River Basin, China - Liu, Yuan; Chen, Weiqiang; Li, Ling; Huang, Junchang; Wang, Xianglong; Guo, Yulong; Ji, Guangxing (Frontiers in Ecology and Evolution, 2023)
The Lancang River Basin (LCRB) is the largest international river in Southeast Asia, and any change in its streamflow, i.e., due to the ecological environment and runoff, may lead to disputes between countries to a certain extent. However, the impact of vegetation change on streamflow in the LCRB needs to be clarified. To assess the impact of vegetation change on streamflow in the LCRB, the functional relationship between Budyko parameter (ω) and Normalized Difference Vegetation Index (NDVI) was first computed for constructing a modified Budyko formula. Finally, we quantitatively estimated the influence of different factors on streamflow variation in the LCRB using the modified Budyko formula and the elastic coefficient method. The conclusions were as follows: (1) A sudden change in streamflow at the Yunjinghong hydrological station appeared in 2005; (2) Budyko parameter (ω) has a good linear functional relationship with NDVI in the LCRB (p < 0.01); ND (3) vegetation variation played the largest driving force behind streamflow variation in the LCRB, accounting for 34.47%. The contribution rates of precipitation, potential evaporation, and anthropogenic activities on streamflow variation from 1982 to 2015 were 16.83, 17.61, and 31.09%, respectively.